Energetic processing of hydrocarbons molecular species by ionizing radiation towards the formation of cyclic species. Issue 14 (January 2020) - Indrajith, S; Kočišekt, J; Domaracka, A; Rousseau, P; Huber, B A
Synopsis: Here we report on experimental studies of the collisions between butadiene clusters and three different ionizing radiation sources: 70 eV electrons, 270 nm photons and 3 keV Ar + ions. New molecular species are produced by growth mechanism inside of clusters.